2014
DOI: 10.1017/s1368980014001141
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12serostatus in Colombian children and adult women: results from a nationally representative survey

Abstract: Objective: Vitamin B 12 deficiency is associated with many adverse health outcomes and is highly prevalent worldwide. The present study assesses the prevalence of vitamin B 12 deficiency and marginal deficiency in Colombian children and women and examines the sociodemographic correlates of serum vitamin B 12 concentrations in these groups. Design: Cross-sectional, nationally representative survey. Setting: Colombia. Subjects: Children <18 years old (n 7243), pregnant women (n 1781), and nonpregnant women 18-49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 40 publications
2
22
0
3
Order By: Relevance
“…Noncausal explanations of the findings are possible because of the observational nature of the study. Vitamin B-12 status in this population is strongly related to socioeconomic conditions (17) and parental education (56). Although we adjusted for these variables in the analysis, it is not possible to completely rule out residual confounding.…”
Section: Discussionmentioning
confidence: 97%
“…Noncausal explanations of the findings are possible because of the observational nature of the study. Vitamin B-12 status in this population is strongly related to socioeconomic conditions (17) and parental education (56). Although we adjusted for these variables in the analysis, it is not possible to completely rule out residual confounding.…”
Section: Discussionmentioning
confidence: 97%
“…15 La prevalencia de deficiencia de vitamina B12, se estableció para este análisis con valores de concentración sérica de B12 inferiores a 222 (pmol/l), en el rango de >= 148 (pmol/l) y <222 (pmol/l) se declaró la deficiencia marginal y por debajo de <148 (pmol/l) la deficiencia declarada. 19 Anemia por deficiencia de hierro. Las concentraciones de hemoglobina (g/dL) fueron obtenidas a partir de una muestra de sangre capilar, con fotómetros portátiles Hemo-Cue AB y 201.…”
Section: Desigualdad Y Nutrición: Encuesta De La Situación Nutricionaunclassified
“…La población de referencia para la AAPL, fue el número de nacimientos, como proximal del número de mujeres que en teoría, debían recibir AAPL. 19,20 Los cálculos para establecer las prevalencia de anemia, déficit de vitamina B12 y ETVVG se realizaron utilizando el software Stata. 21 La información sobre déficit de vitamina B12, anemia y ETVVG fue calculada incorporando el diseño complejo de la muestra, con las bases originales que dieron origen al reporte oficial de las ENSIN-2010.…”
Section: Tablaunclassified
“…Vitamin B 12 deficiency may be more prevalent in vegetarians, vegans, and people living in low-income communities where they may have limited purchasing power to acquire animal food sources or may not have access to fortified foods or supplements (17,18). Koc et al found B 12 deficiency in 41% of newborns in the Southeastern Anatolia Region of Turkey where B 12 deficiency is common (5).…”
Section: Discussionmentioning
confidence: 99%